EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL UNTUK MENINGKATKAN BRAND AWARENESS, FUNCTIONAL BRAND IMAGE, DAN HEDONIC BRAND IMAGE DARI PRODUK â PRODUK SAMSUNG GALAXY - Hartanto, Hendry; Silalahi, Engelbertha (Jurnal Manajemen, 2013)
The use of media as a channel of communication between producers and consumers has been growing rapidly. In connection with this, the authors conducted a study to determine the effectiveness of the use of social media to increase brand awareness, functional brand image, and hedonic brand image. This study used convenience sampling method to spread the questionnaire to 74 respondents. The collected data was tested for validity and reliability, and then analyzed using Analysis of Mean Score, Overall Mean Score, and Multiple Linear Regression. The results of research showed that the perception of traditional media has a significant influence on brand awareness, functional brand image, and hedonic brand image, while the perception of social media has a significant influence on the functional brand image and hedonic brand image, but the perception of social media has no effect on brand awareness.Key words: media sosial, brand awareness, brand image